The expression of GAPDH gene in human blood as early detection of alzheimer's disease - Yusof, Nurdiyana (2015)
Alzheimer's disease (AD) is the most common form of dementia, which is highly heritable and has a complex pattern of etiology (Momeni & Ferrari, 2010). Globally, the prevalence of dementia is estimated to be as high as 24 million. This number is suspected to increase two fold in every 20 years until year 2040 (Mayeux & Stem, 2012). The disease, which has been studied after almost 100 years was named after the investigator's name, Alo is Alzheimer in 1906 (Raja, 2010).